2020
DOI: 10.5888/pcd17.200112
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory Capacity of Anthropometric Indices for Cardiovascular Disease in Adults: A Systematic Review and Meta-Analysis

Abstract: Introduction Obesity is one of the main risk factors for cardiovascular disease (CVD) and cardiometabolic disease (CMD). Many studies have developed cutoff points of anthropometric indices for predicting these diseases. The aim of this systematic review was to differentiate the screening potential of body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) for adult CVD risk. Methods We used relevant key words to search electronic databases to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 64 publications
5
26
0
2
Order By: Relevance
“…In both rats and humans, VAT produced significantly more PAI-1 compared to SAT. These results are consistent with the observation that cardiovascular risk is most closely correlated with central obesity [ 157 ]. PAI-1 produced by adipocytes and vascular endothelium is involved in tissue expansion and angiogenesis necessary during adipose tissue development [ 158 ].…”
Section: Underlying Mechanisms Linking Obesity To Major Complications As a Results Of Sars-cov-2 Infectionsupporting
confidence: 93%
“…In both rats and humans, VAT produced significantly more PAI-1 compared to SAT. These results are consistent with the observation that cardiovascular risk is most closely correlated with central obesity [ 157 ]. PAI-1 produced by adipocytes and vascular endothelium is involved in tissue expansion and angiogenesis necessary during adipose tissue development [ 158 ].…”
Section: Underlying Mechanisms Linking Obesity To Major Complications As a Results Of Sars-cov-2 Infectionsupporting
confidence: 93%
“…Several studies have also shown that AIP has a positive association with non-alcoholic fatty liver disease (NAFLD), advanced subclinical coronary artery disease (CAD), atherosclerosis and obesity; and is a useful and reliable marker for predicting these diseases [6,23,25]. A study on 11,495 Chinese has shown a signi cant and positive linear relationship between AIP and the prevalence of ischemic stroke [5]. Similar to our ndings, A study in Malaysia showed that among lipid pro le, AIP was more positively correlated with TG and more negatively correlated with HDL-C, thus they consider AIP to be the strongest marker in predicting CVDs risk over other indices [24].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing blood pressure and serum cholesterol can, indeed, effectively prevent or delay CVDs events [4].Thus, measuring the risk factors for prediction and early detection of disease can be useful. In a meta-analysis study (2020), CVDs prediction was reported based on simple anthropometric indices including waist circumference (WC), body mass index (BMI) and waist to hip ratio (WHR) [5].Accumulation of visceral fat and blood lipid also are among the numerous risk factors contributing to CVDs [6,7]. Amato et al (2010) introduced visceral adiposity index (VAI), which is a combination of WC, BMI, triglyceride (TG) and high-density lipoprotein cholesterol (HDL-C) [8].…”
Section: Introductionmentioning
confidence: 99%
“…A study on 9,746 participants found that BMI, WC and WHR indices were valid predictors of MetS risk in adult; and BMI had the highest predictive power (AUC: 0.78; 95%CI: 0.77, 0.80) [18]. Meta-analysis studies have also reported these indicators as a reliable tool for predicting CVDs and MetS [19,20].…”
Section: Discussionmentioning
confidence: 99%